Lo sviluppo sostenibile ed il turismo - Enza Zabbini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
– This paper aims to introduce the paradigm of the sustainability in a didactic contest, to explain how a revolutionary concept can be applied in a particular sector as the tourism, that, with his transversality and his transdisciplinarity, culd be a good field to start or to spread a new way to organise the territory.
Keywords: 330